The findings of 18(F)-fluorodeoxyglucose positron emission tomography–computed tomography scan in patients with hidradenitis suppurativa in Malaysia: A multicenter study - Loo, Chai Har (World J Nucl Med, 2020)
Hidradenitis suppurativa (HS) is known to have association with systemic diseases with chronic inflammation such as psoriasis. We aim to describe the concomitant systemic inflammation in patients with HS using 18F-fluorodeoxyglucose positron emission tomography–computed tomography ((18)F-FDG PET/CT) scan. This was a case–control study conducted in three tertiary hospitals in Northern Malaysia from January to December 2017, involving HS patients aged 18 years and above. Thirty-two HS patients with age- and sex-matched controls were recruited with a mean age of 31.4 years (range: 18–56). Numerous cutaneous inflammatory foci were detected on FDG-PET/CT scan in clinically unapparent sites (27/32, 84.4%). Approximately 90.6%, 93.8%, and 50.0% of the patients had significantly higher cutaneous uptake over nasal, mandibular, and scalp regions, respectively (P < 0.0001). PET/CT scan did not detect any systemic inflammation unlike those found in psoriasis. Three (9.4%) patients had thyroid nodules with high uptake (maximum standard uptake values ranging from 2.9 to 11.3). Two of them were confirmed to have papillary thyroid carcinoma, while the third patient has inconclusive finding. (18)F-FDG PET/CT scan may be useful to map disease burden of HS. Nonlesional inflammatory foci on the skin of the nose, mandibular, and scalp are probably significant. The association of thyroid carcinoma in HS warrants further evaluation.